Математичне моделювання рефлексивного управління - Taran, T. A.; Shemaev, V. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The main principles of mathematical theory of reflective behavior are considered in the paper. Boolean models of many-valued reflective choice are investigated. Formal conditions of the reflexive control are found on the base of suggested models.